PENGUATAN KOMPETENSI SISWA KEBUMIAN MELALUI PEMBINAAN TERSTRUKTUR DAN PRAKTIKUM LAPANGAN UNTUK PERSIAPAN OSN TINGKAT KABUPATEN - Syafrizal, Syafrizal; Muliani , Muliani; Novita, Nanda; Fatwa, Islami; Darisma , Dian (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2025)
Earth science is one of the science fields competed in the National Science Olympiad (OSN) for Senior High Schools (SMA). However, not all schools provide earth science as a separate subject, so students often face difficulties in learning complex and multidisciplinary materials. This community service activity was carried out to train students to face the selection of OSN at the district/city level through structured coaching and field practicums in strengthening student competency in the field of earth science. The method of implementing the activity includes 3 stages, namely the preparation and coordination stage, implementation of activities, evaluation, and follow-up. The results of the activity showed a significant increase in student competency in the field of earth science, on average posttest scores in the range (65-80) compared to the pretest (25-40) on each topic of material, which was also reinforced by the results of the Quizizz application-based practice questions. In the school-level selection, five students were successfully selected to continue to the district-level OSN, and one of them achieved an achievement at that level. Overall, this community service activity has not only succeeded in improving students' academic readiness to face OSN but also strengthened the culture of scientific learning, observation skills, and collaboration between universities and schools to produce a superior young generation in the field of earth sciences.